Ethyl chitosan synthesis and quantification of the effects acquired after grafting it on a cotton fabric, using ANOVA statistical analysis. (15th March 2016) - Popescu, Vasilica; Muresan, Augustin; Popescu, Gabriel; Balan, Mihaela; Dobromir, Marius
Highlights: Synthesis of triethyl chitosan using ethyl chloride as alkylation agent. Alkylation and grafting were confirmed by FTIR, 1 H NMR, XPS, DSC, TGA/DTG. Quantified results: take-up degree, wrinkle-recovering angle, tensile strength. ANOVA shows the maximal effects of chitosan, ethyl chloride and their interaction. Durability of effects was highlighted with tinctorial and diffusimetric methods. Abstract: Three ethyl chitosans (ECSs) have been prepared using the ethyl chloride (AA) that was obtained in situ. Each ECS was applied on a 100% cotton fabric through a pad–dry–cure technology. Using the ANOVA as statistic method, the wrinkle-proofing effects have been determined varying the concentrations of AA (0.1–2.1 mmol) and chitosan (CS) (0.1–2.1 mmol). Alkylation and grafting mechanisms have been confirmed by the results of FTIR, 1 H NMR, XPS, SEM, DSC and termogravimetric analyses. The performances of each ECS as wrinkle-proofing agent have been revealed through quantitative methods (taking-up degree, wrinkle-recovering angle, tensile strength and effect's durability). The ECSs confer wrinkle-recovering angle and tensile strength higher than those of the witness sample. Durability of ECSs grafted on cotton have been demonstrated by a good capacity of dyeing with non-specific (acid/anionic and cationic) dyes under severe working conditions (100 °C, 60 min) and a good antimicrobial capacity.